2018
DOI: 10.28982/josam.432629
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of microdose flare up and flexible antagonist protocols in poor responders undergoing IVF treatment: A prospective randomized controlled trial

Abstract: How to cite / Atıf için: Özdoğan S, Özdeğirmenci Ö, Dilbaz S, Demir B, Çınar Ö, Dilbaz B, Göktolga Ü. The comparison of microdose flare up and flexible antagonist protocols in poor responders undergoing IVF treatment: A prospective randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another study, Özdoğan et al showed that the PR was non-significantly more in micro-dose protocol while the days of stimulations and a total dosage of gonadotropins were non-significantly more in the antagonist group (21). Moreover, Kahraman et al found that the clinical PR was non-significantly more elevated in the micro-dose group (22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, Özdoğan et al showed that the PR was non-significantly more in micro-dose protocol while the days of stimulations and a total dosage of gonadotropins were non-significantly more in the antagonist group (21). Moreover, Kahraman et al found that the clinical PR was non-significantly more elevated in the micro-dose group (22).…”
Section: Discussionmentioning
confidence: 98%
“…Studies comparing the micro-dose regimen with the antagonist regimen in treating women with a reduced response (18)(19)(20)(21)(22)(23) are relatively less in comparison to those comparing the antagonist with agonist flare-up protocol in POR women undergoing ICSE-ET (24)(25)(26)(27)(28)(29)(30). Furthermore, there is still a debate on the effectiveness of these three protocols.…”
Section: Discussionmentioning
confidence: 99%